Internalization mechanisms of cell-penetrating peptides - Ruseska, Ivana; Zimmer, Andreas (Beilstein journal of nanotechnology, 2020)
In today’s modern era of medicine, macromolecular compounds such as proteins, peptides and nucleic acids are dethroning small molecules as leading therapeutics. Given their immense potential, they are highly sought after. However, their application is limited mostly due to their poor in vivo stability, limited cellular uptake and insufficient target specificity. Cell-penetrating peptides (CPPs) represent a major breakthrough for the transport of macromolecules. They have been shown to successfully deliver proteins, peptides, siRNAs and pDNA in different cell types. In general, CPPs are basic peptides with a positive charge at physiological pH. They are able to translocate membranes and gain entry to the cell interior. Nevertheless, the mechanism they use to enter cells still remains an unsolved piece of the puzzle. Endocytosis and direct penetration have been suggested as the two major mechanisms used for internalization, however, it is not all black and white in the nanoworld. Studies have shown that several CPPs are able to induce and shift between different uptake mechanisms depending on their concentration, cargo or the cell line used. This review will focus on the major internalization pathways CPPs exploit, their characteristics and regulation, as well as some of the factors that influence the cellular uptake mechanism.